Peripheral BDNF and psycho-behavioral aspects are positively modulated by high-intensity intermittent exercise and fitness in healthy women - de Poli, Rodrigo Araujo Bonetti [UNESP]; Lopes, Vithor Hugo Fialho [UNESP]; Lira, Fábio Santos [UNESP]; Zagatto, Alessandro Moura [UNESP]; Jimenez-Maldonado, Alberto; Antunes, Barbara Moura [UNESP] (Springer Nature, 2021)
Acute high-intensity intermittent exercise (HIIE) induces the myokine secretion associated with neurogenesis, as well brain-derived neurotrophic factor (BDNF); however, it remains unknown how the menstrual phase influences this secretion after an acute exercise session. The current study aimed to investigate the effects of HIIE performed in luteal and follicular menstrual phases on BDNF, cognitive function, mood, and exercise enjoyment. Fourteen healthy women completed four experimental sessions, randomly. One graded exercise test (GXT) and one HIIE session (10 × 1-min runs 90% peak GXT velocity [1-min recovery]) were performed for each menstrual phase. Blood samples were collected at rest and immediately after efforts, and the profile of mood states questionnaire (POMS) and Stroop-task test were applied. During the HIIE, subjective scales were applied (feeling, felt arousal, rate of perceived exertion, and physical activity enjoyment). The main results showed that the serum BDNF presented no difference between menstrual phases (p = 0.870); however, HIIE increased BDNF concentration in both menstrual phases (p = 0.030). In addition, the magnitude of circulating BDNF variation (Δ%BDNF) and V ˙ O 2max demonstrated an inverse relationship in the follicular phase (r = − 0.539, p = 0.046), whereas in the luteal phase, Δ%BDNF was negatively correlated with time test (r = − 0.684, p = 0.007) and RPE (r = − 0.726, p = 0.004) in GXT. No differences between menstrual phases were observed for POMS (p ≥ 0.05); however, HIIE attenuated tension (p < 0.01), depression (p < 0.01), and anger moods (p < 0.01), independently of menstrual phases. The subjective scales and Stroop-task test did not show differences. In conclusion, menstrual cycle phase does not affect serum BDNF levels, cognitive function, mood, and exercise enjoyment. Contrary, HIIE increases peripheral BDNF and attenuates tension, depression, and anger independently of menstrual phase. In addition, Δ%BDNF was correlated with physical fitness in the follicular phase, exhibiting higher changes in women with lower physical fitness status.